Work-family conflict across the lifespan - Huffman, Ann; Culbertson, Satoris S.; Henning, Jaime B.; Goh, Adrian (My University, 2013)
Purpose: Research on work-family conflict has primarily focused on younger workers, with little attention paid to workers across the lifespan. To address this gap, the current study examined work-family conflict for individuals aged 18 to 70, focusing on explanations for why age is differentially related to work-family conflict at different points in one’s life. Design: Hypotheses were tested using data from two independent samples of working adults from the National Study of the Changing Workforce (N = 3,552 and 2,852, respectively). Results: Results supported a curvilinear relationship with youngest and oldest workers having the fewest conflicting demands between work and home. Further, results demonstrated that family satisfaction and the age of youngest child help explain why these workers are less likely to experience family interference with work. Finally, work hours were found to mediate the relationship between age and work interference with family. Originality/Value: One of the most substantial demographic transformations in the general population involves the aging of the workforce. This is one of the first papers to examine and provide insight into why age is related to work-family conflict.
Keywords: Work-family conflict; Age; Lifespan